Not-so-simple stellar populations in star clusters : doctoral thesis accepted by the Department of Astronomy at Peking University, Beijing, China /: doctoral thesis accepted by the Department of Astronomy at Peking University, Beijing, China. (2017) - Li, Zhengyuan
No abstract available